Assessing the sensitivity and specificity of First Response HIV-1-2 test kit with whole blood and serum samples: a cross-sectional study. Issue 1 (December 2016) - Boadu, Raymond; Darko, George; Nortey, Priscilla; Akweongo, Patricia; Sarfo, Bismark
Abstract Background Human immunodeficiency virus (HIV) Rapid diagnostic Test (RDT) kits are the preferred assays for HIV testing in many countries. Prevention of Mother-to-Child Transmission, Know Your Status Campaigns, Blood-Safety, Voluntary Counseling and Testing are major strategies adapted to control transmission of the virus and the pivot of these interventions is either screening or diagnosing individuals through testing. There are reports of inconsistent sensitivity and specificity with whole blood and serum samples collected from the same individual. Little is known about the diagnostic characteristics of First Response HIV-1-2 RDT kit, used as a single test kit in national HIV prevention and control programmes. The debate has always centered on choosing between whole blood and serum in a case where a single test kit that runs on only blood specimen will be used for testing. The variations in specificities and sensitivities with whole blood and serum samples imply that some individuals who might be true positives will be missed and elude care. This study determined the best blood-based specimen type (whole blood or serum) that improves performance of First Response HIV RDT kit in detecting HIV-specific antibodies. Methods A hospital-based cross-sectional study was conducted on 280 HIV infected and non-infected patients from May 2015 to June 2015. Blood samples from each participant were separated into whole blood and serum, and tested on First Response HIV-1-2 kits (Premier Medical Corporation Ltd., Kachigam, India) using Electro-chemi-luminescence assay (ECLIA) as reference assay. Results First Response HIV-1-2 RDT kit showed 100 % sensitivity and 100 % specificity with whole blood specimen and 100 % sensitivity and 82.86 % specificity with serum specimen for the detection of HIV-1. The positive and negative predictive values were 100, 100 and 85.35, 82.86 % for whole blood and serum respectively. Conclusion Whole blood specimen(s) from an individual have higher specificity, positive and negative predictive values than serum. Whole blood is the primary specimen to use on First Response HIV-1-2 RDT kit when screening peripheral blood for HIV-1-specific antibodies.